lntroducing a selective dynamics releasing frame algorithm to speed-up stochastic aggregation computer simulations - Montenegro J., Javier (2002)
A faster algorithm, the selective dynamics releasing frame (SORF), to computer-simulate the stochastic aggregation of diffusing particles is introduced. The SORF is presented making reference to the OLA model of Witen & Sander, however it can be applied to any OLA-Iike model which simulates cluster growth by diffusion. Traditional OLA-like models use the longest radius of the growing aggregate to control the radius of a Circular Launching Frame from where the particles are released to diffusion. The SORF uses the different radii of the regions of the growing cluster to fix a particular distance from where to release the particles to diffusion in every region. In bi-dimensional OLA simulations, a reduction in 30% of computer time was observed when the SORF was used. The algorithm here introduced is for a bi dimensional simulation, however its application to higher dimensions is straightforward. © 2002 CSI. Al! rights reserved